Surgical Procedures for Hip Joint Preservation for Osteonecrosis of the Femoral Head: A Bibliometric Analysis. (13th February 2021) - Zhang, Qingxi; Li, Hui; Zhao, Yu; Xing, Dan; Lin, Jianhao
Abstract : Background and Objective . Studies have concentrated on the surgical procedures for hip joint preservation for osteonecrosis of the femoral head (ONFH). This study is aimed at presenting a bibliometric analysis of the relevant articles published from 1999 to 2019. Method . Articles which concentrated on surgical procedures for hip joint preservation for ONFH were searched using Web of Science database. The data were analyzed by using bibliometric analysis. Additionally, VOS viewer software was used for bibliographic coupling, coauthorship, cocitation, and cooccurrence analyses and to investigate the publication trends of the mentioned field. Results . A total of 3467 articles were included. China had the highest number of relevant published articles. However, the USA made the highest contributions to the global research with the highest citations and h -index. The journal of Clinical Orthopaedics and Related Research published the highest number of relevant articles. Studies could be classified into four clusters: "process and clinical treatment, " "risk factors and diagnosis, " "pathophysiology, " and "basic research." "Pathophysiology" and "basic research" clusters were predicted as the next hot topics of surgical procedures for hip joint preservation for ONFH. Conclusion . Based on the current global trends, the number of published articles related to surgical procedures for hip joint preservation for ONFH has increased. The USA was noted as the leading country in global research in the target field. "Pathophysiology" and "basic research" clusters may be the next hot spots, and scholars need to further concentrate on the target topic.